APPLICATION OF FUZZY SET METHODS FOR MAKING LOGISTIC DECISIONS IN MODERN CONDITIONS - HEIDAROVA, Olena; DRAINA, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the application of the methodology of forecasting the results of logistics activities of the enterprise by ranking the criteria. Logistics activities of business entities affect the environment and various aspects of the regions where it is carried out. Traditional approaches to assessing the results of logistics activities of business entities do not meet modern challenges, since they do not allow taking into account economic, social and environmental aspects, that is, they are not able to ensure the sustainable development of the enterprise. There is a need to find new methods for assessing the results of logistics activities of the enterprise, which should take into account the main components of development: economic, social, environmental and innovative. In the process of managing the logistics activities of the enterprise, it is necessary to identify possible risks, evaluate them taking into account the factors of influence on logistics processes, as well as make managerial decisions to protect against them. Processing of fuzzy quantitative and qualitative information for making logistic decisions and finding the optimal result can be obtained using methods: maximin convolution; fuzzy preference ratio; fuzzy logical conclusion; additive convolution, etc. As input parameters, it is proposed to choose the cost of products (services), the price of products (service) and the volume of sales (provision), taking into account the uncertainty factor. To obtain numerical values of different weights of input parameters, we use, according to the method of analyzing hierarchies, the method of pairwise comparisons. The use of the maximum convolution method in determining the desired diagnosis involves choosing a minimum value or a maximum value from the entire set of belonging functions. The method of ranking different weights of input criteria for forecasting the results of logistics activities of a business entity is proposed.